BIOGRAFI DOKTER MAYOR R.M SOEMITRO SEBAGAI PEJUANG RIAU TAHUN 1942-1950 - Fadilah Rachman; Bedriati Ibrahim; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Doctor Major R. M. Soemitro was a Doctor graduated from STOVIA medical school in 1935, he was a figure of Riau fighter who came from Java Island precisely in Pekalongan, Central Java. Being a graduate of a medical school during Dutch rule in Indonesia, he was assigned to work on several major islands in Indonesia such as on the island of Kalimantan, Java and Sumatra. Transfer of duties to the island of Sumatra, he was assigned to Selatpanjang because at that time there was an epidemic and the Selatpanjang General Hospital lacked medical personnel. The research objectives carried out by the author include To find out the profile of the Doctor Major R.M Soemitro, to find out the role of the doctor Major R.M Soemitro as a Riau fighter in 1942-1950. To find out the end of the struggle of Doctor Major R. M. Soemitro in exile by the Dutch and to find out the process of transferring the tomb of Doctor Major R. M. Soemitro. The method used by the author is histroriography method which emphasizes on four stages, namely heuristics, verification, interpretation and historiography. Japan's defeat against the allies caused the situation to be difficult for the Japanese government to continue to rule in Indonesia. The government vacuum in Bengkalis was immediately taken over by the Chinese, the Bengkalis people who did not receive it agreed to appoint a Doctor Major R.M Soemitro to be their leader, this was the beginning for him to take up arms in Riau. In 1946 Doctor Major R.M Soemitro joined TKR / BKR Bengkalis, then in Rengat immediately formed a V Regiment under the leadership of Major Toha Hanafi and he was appointed as Health Major. During the Dutch Military Aggression in Rengat he was taken prisoner by the Dutch and exiled to Penuba Island.Keywords: Doctor Major R. M. Soemitro, Riau Fighters